PERUBAHAN MASYARAKAT PETANI MENJADI NELAYAN (STUDI KASUS DI KECAMATAN AYAH KEBUMEN) (Forum Ilmu Sosial, 2008)
Kebumen regency geographically can be distinguished into three areas. They are the mountain area innorth, the beach area in south, and the middle area. Ayah sub district has two different areas geographically.The south and west areas are lowland (beaches), while the north and middle areas are upland. Ayah subdistrict consists of 18 villages, which are 5 of them be contiguous with sea, so they are called beachesareas. Among the beaches in Ayah Sub district, Logending beach, Pedalen beach, and Pasir beach are thecenter of fishermen activities. Logending beach lays in west area, border on Jetis beach in Cilacap regency,Pasir beach lays in east area, near Karangbolong, and Pedalen beach lays between Logending beach andPasir beach. The growth of fishermen community in Kebumen south beach is uncommon because of itsgeographic factor. This issue makes an interesting study in this article. The data to study the fishermenlife are gained through documentation, library, interview, and field observation studies. Then, all of thoseinformation are processed and presented descriptively, so they can be understood easily.Keywords: Farmer, fishermen, Ayah subdistrict